Emergency medicine transformation to improve hospital admissions and patient outcomes: Emergency ambulatory care model in Hong Kong - Shin Yan Man; Kwong Hang Yeung; Chi Hung Cheng; Nai Kwong Cheung; Ralph Koon Ho Cheung; Lee Kwan Chuk (Hong Kong Journal of Emergency Medicine)
Abstract Introduction The Prince of Wales Hospital's Emergency Ambulatory Care (EAC) service, initiated in August 2021, exemplifies an innovative approach to the emergency department (ED) to address the increasing demands on healthcare systems. This study evaluates the impact of EAC service on hospital admissions, focusing on patients with ambulatory care‐sensitive conditions over the initial 5 months. Methods A retrospective cohort study was conducted to evaluate the EAC service from 1 August 2021 to 31 December 2021. The service integrated the ED's workflow and operated 171 eight‐hour sessions. Descriptive statistics and the Spearman correlation test were used in the analysis. Results A total of 408 patients were recruited and the service achieved a high discharge rate of 89.5%, contributing to a 7.5% reduction in hospital admissions for medical conditions. These results were supported by a significant negative correlation (r = −1.000, p < 0.001) between the number of EAC sessions provided and the average daily percentage of patients admitted to the medical wards, underscoring the service's capacity to alleviate hospital admission rates. Furthermore, it achieved a low rate of 30‐day all‐cause mortality of 1.0%, without any intensive care unit admission, and an unscheduled ED re‐attendance rate of 4.7%. Conclusions The EAC service's successful implementation and outcomes demonstrate its potential to transform emergency care delivery, offering a sustainable alternative to traditional inpatient hospitalization for acute medical conditions. This research contributes to the ongoing discussion on optimizing healthcare delivery, emphasizing the need for innovative models like the EAC to improve system efficiency and patient outcomes in the face of growing healthcare challenges.